AB0682 Predictive Factors of Bad Pulmonary Outcome at Three Years in a Single Centre Cohort of Patients with Connective Tissue Disease-Associated Interstitial Lung Disease. (9th June 2015) - Franco, C.; Carballosa, P.; Sanchez Pernaute, O.; Familiar, V.; Rodriguez Nieto, M.J.; Martinez Becerra, M.J.; Martinez Carranza, R.; Gomez Seco, J.; Herrero Beaumont, G.; Romero Bueno, F.
Abstract : Background: The natural course of Interstitial Lung Disease (ILD) in patients with Connective Tissue Disease (CTD) is unpredictable and markers identifying candidates for the available therapies are needed. Objectives: We investigated predictive factors of bad pulmonar outcome in our patients with CTD-associated ILD (CTD-ILD). Methods: Retrospective-prospective review of medical records of patients with CTD-ILD attending our Unit who completed three years follow-up. Data on clinical and laboratory parameters and pulmonary function tests (PFT) were collected at baseline (T0), 6 months (T6m) and 3 years (T3). Lung functional status (LFS) was defined as normal or restricted according to forced vital capacity (FVC), diffusing capacity for carbon monoxide (DLco) values, and alveolar volume adjusted DLco (Zco). Data are expressed as frequencies, or median (IQR). Regression models were employed to assess interference between cofactors and adjust estimate values. Results: At baseline, the 35 recruited patients (28 women; age 66 y) had a disease duration of 5 (3) years. ILD patterns were Usual Interstitial Pneumonia (UIP) in 51%, Non-Specific Interstitial Pneumonia (NSIP) in 23%, Cryptogenic Organizing Pneumonia (COP) in 2 cases, Desquamative Interstitial Pneumonia (DIP) in 1 patient and an unclassified ILD in 23% of the patients. LFS at T0 was normal in 9 patients (26%) and altered in 74%, of which 6 patients had mild, 13 moderate, and 7 severe restriction. At T3, LFS was normal in 8 (23%) patients, with 3 (9%), 13 (37%) and 8 (23%) showing mild, moderate or severe restriction, respectively. The ILD course was rapidly progressive in one patient. Five patients (14%) had a fatal outcome: 4 of them with UIP. Compared to NSIP, UIP was associated with PFT deterioration or death (p 0.054). The presence of dyspnea at baseline and pulmonary related hospital admission during the observation period predicted a poorer outcome. Higher triglyceride levels were found related to a fatal outcome (p 0.016) and/or an end-stage disease (p 0.058). Induction treatment with methylprednisolone or immunomodulating drugs during the first 6 months led to a significant increase in FVC at T6m (p<0.001), but had little impact in the other functional parameters. Myositis associated autoantibodies predicted an FVC improvement at T6m (p 0.048), while pulmonary comorbidity at T0 was associated with FVC and DLco deterioration at T6m (p 0.02 and p 0.03, respectively). Lower DLco values at baseline and at T6m was the strongest predictor of an end-stage disease (or death) at T3. The association was also significant when adjusted by modifiers, including age, ILD pattern, BAL findings or positive RF tests, all of which were associated to a poorer outcome. Conclusions: Our result indicate that patients with low DLco values evolve to end-stage disease and are probably resistant to current therapies. The relevance of additional prognostic markers, such as the presence of myositis associated antibodies or levels of triglycerides, should be addressed in future studies. Disclosure of Interest: None declared